2021
DOI: 10.47815/apsr.2021.10085
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and water use efficiency of kinnow mandarin (citrus reticulate blanco) as influenced by drip trickle irrigation and hydrogel

Abstract: An experiment was conducted to find out the effect of drip trickle irrigation and hydrogel with black polyethylene mulch on productivity and water use efficiency of Kinnow mandarin. The two years pooled data revealed that highest available nitrogen, phosphorus and potassium (244, 20 and 164 kgha-1), porosity and maximum water holding capacity (34.5 and 40.9 %) and percent increase height, spread and canopy volume (13.6, 14.8 and 44.5 %), respectively, were obtained with the application of 3 days drip trickle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…These results along with the previous studies indicate that mulching plays an important role in the conservation and retention of soil moisture in the root zone [5][6][7][8]. It has also been shown that drip irrigation with mulch improves soil moisture in citrus and other crops [9][10][11]16]. The review by Chai et al (2016) indicated that regulated drip irrigation (RDI) improves tree growth, as well as soil moisture under drought stress [27].…”
Section: Sensor-based Soil Moisture Distribution In the Irrigated Zonementioning
confidence: 51%
See 1 more Smart Citation
“…These results along with the previous studies indicate that mulching plays an important role in the conservation and retention of soil moisture in the root zone [5][6][7][8]. It has also been shown that drip irrigation with mulch improves soil moisture in citrus and other crops [9][10][11]16]. The review by Chai et al (2016) indicated that regulated drip irrigation (RDI) improves tree growth, as well as soil moisture under drought stress [27].…”
Section: Sensor-based Soil Moisture Distribution In the Irrigated Zonementioning
confidence: 51%
“…The practice of mulching helps with the proper growth and development of plants by modifying soil temperature, providing better nutrient availability, and by better water conservation [8]. In the study on kinnow mandarin, drip irrigation with black-polyethylene mulch significantly improved the soil moisture content, yield, and fruit quality over bare ground [9,10]. Drip irrigation and plastic mulch also increased soil moisture content (41%) in Kinnow mandarin [11].…”
Section: Introductionmentioning
confidence: 99%